Factors of decreasing students interest when learning from home - Siswi Dewi Mardianti (ETUDE: Journal of Educational Research, 2021)
Background: Distance learning is one solution to replace offline learning, with distance learning. foster interest in learning for students because without interest the learning objectives will not be achieved. However, the implementation of the current distance learning system does not rule out the emergence of several problems in the learning process. Starting from the limited facilities of students, lack of understanding of the use of technology, the difficulty of internet networks in some areas where they live. Purpose: This research aims to find out what causes the decline in interest in learning in low-level elementary school students in distance learning. Design and methods: This research uses one type of descriptive qualitative research with a case study method or approach. The subjects of this study were elementary school teachers, parents, and low-level elementary school students. The technique that researchers use in collecting data is the data triangulation technique. Results: The research result states that the factors that cause a decline in the learning interest of low-level elementary school students during distance learning are caused by several internal and external factors.